L’affirmation du tequila, référence identitaire, succès commercial et première « Indication Géographique » du Mexique - Margarita Franco Gordo; Jean-Christian Tulet (Caravelle)
During the last decades, tequila has become important as an identity reference officially recognized for the creation of a « geographical Identity », as well as for the considerable development of its consumption. Slowly, tequila becomes one of the world’s best known drinks, even if it’s mainly drank in Mexico and the United States. This fact comes along with a very important change in the ownership of its main enterprises which practically all now belong to non Mexicans. A very great effort has been done as well in the control of the quality and origin of the product, effort in which the « Consejo Regulador del Tequila » plays a mayor part.